Aerobic capacity according to playing role and position in elite female basketball players using laboratory and field tests - Scanlan, A. T.; Stojanovic, E.; Milanovic, Z.; Teramoto, M.; Jelicic, M.; Dalbo, V. J. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To compare the aerobic capacity of elite female basketball players between playing roles and positions determined using maximal laboratory and field tests. Methods: Elite female basketball players from the National Croatian League were grouped according to playing role (starter: n = 8; bench: n = 12) and position (backcourt: n = 11; frontcourt: n = 9). All 20 players completed 2 maximal exercise tests in a crossover fashion 7 days apart. First, the players underwent a laboratory-based continuous running treadmill test with metabolic measurement to determine their peak oxygen uptake (VO2peak). The players then completed a maximal field-based 30-15 Intermittent Fitness Test (30-15 IFT) to estimate VO2peak. The VO2peak was compared using multiple linear regression analysis with bootstrap standard errors and playing role and position as predictors. Results: During both tests, starters attained a significantly higher VO2peak than bench players (continuous running treadmill: 47.4 [5.2] vs 44.7 [3.5] mL/kg·min, P = .05, moderate; 30-15 IFT: 44.9 [2.1] vs 41.9 [1.7] mL/kg·min, P < .001, large), and backcourt players attained a significantly higher VO2peak than frontcourt players (continuous running treadmill: 48.1 [3.8] vs 43.0 [3.3] mL/kg·min, P < .001, large; 30-15 IFT: 44.2 [2.2] vs 41.8 [2.0] mL/kg·min, P < .001, moderate). Conclusions: Starters (vs bench players) and guards (vs forwards and centers) possess a higher VO2peak irrespective of using laboratory or field tests. These data highlight the role- and position-specific importance of aerobic fitness to inform testing, training, and recovery practices in elite female basketball.